Regulation and function of Bcl-2 during differentiation-induced cell death in HL-60 promyelocytic cells. - Benito, A. (1995)
Polymorphonuclear leukocytes are generated by differentiation of early myeloid precursors. Once fully differentiated, blood neutrophils are programmed to die rapidly and are removed by tissue macrophages. In normal myeloid cells, the death mechanism seems to be coupled to the differentiation pathway and is accomplished by a process termed apoptosis. In the present study, we have examined the role of Bcl-2 in the differentiation pathways of the promyelocytic cell line HL-60. Treatment of HL-60 with retinoic acid or phorbol ester, which induced neutrophil or macrophage-like cell differentiation, respectively, resulted in progressive loss of cellular viability and internucleosomal DNA degradation. In HL-60, differentiation and apoptosis were coupled to down-regulation of the Bcl-2 protein. Overexpression of Bcl-2 by gene transfer inhibited apoptosis triggered by terminal differentiation of HL-60. Yet, Bcl-2 did not alter the expression of surface markers or other phenotypic changes that are induced upon myeloid differentiation. In contrast to HL-60, another immature myeloid cell line, K562, did not produce Bcl-2 but expressed a related protein, Bcl-xL, that functions as a repressor of apoptotic cell death. K562 has been shown to be relatively resistant to a variety of apoptotic stimuli. Incubation of HL-60 and K562 with inhibitors of macromolecular synthesis induced apoptosis, which appeared earlier in HL-60 than in K562. Interestingly, Bcl-2 overexpression protected K562 cells from apoptosis induced by inhibitor of macromolecular synthesis but it had little or no effect on HL-60 cells. We conclude that although differentiation and apoptosis proceed simultaneously, they can be uncoupled by expression of Bcl-2. Down-regulation of Bcl-2 appears to be part of the differentiation pathway and may serve to facilitate the apoptotic response.